Developing Sustainable Procurement System Based on Enterprise Resource Planning - Icca Mita Monica; Ari Yanuar Ridwan; Umar Yunan K.S. Hediyanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Seeing the increasing competition in the manufacturing industry, the implementation of Sustainable Supply Chain Management (SSCM) can be a solution to improve the efficiency of a company's supply chain and also increase competitiveness with competitors. PT. Elco Indonesia Sejahtera is a company engaged in the leather tanning industry located in Garut, West Java. This company does not yet have a system to support the implementation of Sustainable Supply Chain Management in its business processes, including for the procurement department. In addition, the company also does not have a system to monitor its business processes. Therefore, this study aims to design an integrated information system for the procurement department using a system based on Enterprise Resource Planning (ERP), as well as to design a monitoring dashboard so that business processes can be more effective, efficient, and of course, able to manage SSCM well. The results of this study are in the form of a system design and a monitoring dashboard based on ERP to support the implementation of SSCM.